1999
DOI: 10.1063/1.123922
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atomic structure on the formation of electrical barriers at grain boundaries in SrTiO3

Abstract: An experimental atomic resolution analysis of an undoped Σ5 36° [001] tilt grain boundary in SrTiO3 shows that the structure contains incomplete oxygen octahedra. These incomplete octahedra act as effective oxygen vacancies and lead to a fixed, positive boundary charge. Annealing the boundary in the presence of MnO2 does not change the atomic structure of the boundary plane, and results in a high concentration of Mn3+ (acceptor) enrichment at the specific Ti4+ locations in closest proximity to the effective ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 11 publications
0
49
2
Order By: Relevance
“…Conversely, previous studies on STO have attributed a smaller ratio to oxygen deficiency at the core of dislocations or grain boundaries, [14,15,30,33] and furthermore incomplete oxygen octahedra at such defect sites. [34] Our results thus, suggest that the fine structure changes observed in the O-K edge at the dislocation core are the signature of oxygen deficiency. This is not unexpected; for excess Pb atoms to be accommodated in the SRO lattice, they would have to be closer to each other in the extra-half planes due to their larger ionic radii (discussed later).…”
mentioning
confidence: 85%
“…Conversely, previous studies on STO have attributed a smaller ratio to oxygen deficiency at the core of dislocations or grain boundaries, [14,15,30,33] and furthermore incomplete oxygen octahedra at such defect sites. [34] Our results thus, suggest that the fine structure changes observed in the O-K edge at the dislocation core are the signature of oxygen deficiency. This is not unexpected; for excess Pb atoms to be accommodated in the SRO lattice, they would have to be closer to each other in the extra-half planes due to their larger ionic radii (discussed later).…”
mentioning
confidence: 85%
“…Polycrystalline perovskites have a wide range of applications, such as oxygen ion conductors in sensors, diverse electronic devices as varistors, 8,9 piezoelectric materials in actuators, dielectric materials in capacitors, and as substrate for thin film growth of high T c superconductors. 10 Examples where the macroscopic properties of these materials depend critically on the grain boundary structures and the intergranular films include increased toughness, [11][12][13] reduced ionic conductivity, 9,[14][15][16][17] diminished creep resistance, 18,19 tunable electrical conductivity, 20,21 decreased thermal conductivity, 22 and enhanced sintering behavior. 23 The reason for this dominance is that interfaces inherently contain a concentration of defects and dopants far in excess of the equilibrium distribution in the bulk of the material.…”
Section: Introductionmentioning
confidence: 99%
“…1), and was heat-treated at 700°C for 1 h. The electrodes were of 5 mm × 3 mm. The measurements were made at 450°C in air in the frequency range of 0.1-10 7 Hz by a dielectric/ impedance analyzer (Model Alpha-N, Novocontrol, Germany). The HRTEM work was carried out at 1.25 MeV using the Stuttgart JEOL JEM-ARM1250 with 0.12 nm point-to-point resolution.…”
Section: Methodsmentioning
confidence: 99%
“…[5] The consequent electrostatic potential obstructs the transport of charge carriers across the grain boundary. For pure, undoped SrTiO 3 , Kim et al, [6] using electron energy loss spectrometry (EELS), showed that the ratio of Ti to O concentration in various boundaries is higher than in the bulk, indicating that the grain boundaries are enriched in Ti or deficient in O. Browning et al [7] reported that a ∑5 grain boundary (∑ denotes the reciprocal of the fraction of common lattice points of the adjoining grains) is segregated by oxygen vacancies. Klie and Browning [8] reported the segregation of oxygen vacancies at a grain boundary (nominally undoped with a 58°/[001] tilt) in SrTiO 3 , which was compensated by a decrease in the Ti valence.…”
mentioning
confidence: 97%